(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed at examining as well as analyzing the use of the online trading model. The variables of the current study were attitude and perception of the use of online trading, moderated by university students’ interests in Papua- Indonesia. The population of this study were five universities namely, STIEM Bongaya Makasar, Universitas Yapis Papua Jayapura (UNIYAP); Universitas Cenderawasih (Uncen); Universitas Science & Technology Jayapura (USTJ); Universitas Ottow & Geissler Papua (UOGP). The research sample was 97 students incorporated in the Capital Market Study Group and Trading Shares listed on the Indonesia Stock Exchange. It was a kind of incidental sampling. The data were analyzed through SPSS with two path analysis techniques. The results showed that attitude has a positive and significant influence on the use of online trading. In contrast, the perception of usage does not significantly affect the use of online trading. Next, interest in mediating the effect of attitude towards the use of online trading, and interest in partially mediating the influence of the perception of online trading usage.